Marching On - Synnos, Nicos (My University, 2022)
“Proof that inadequate, even childish measures, may serve to rescue one from peril” (Frans Kafka, The Silence of the Sirens, 1931). Kafka’s subversive retelling of the encounter between Odysseus and the alternatively silent Sirens has Odysseus plug his ears with wax and chained to the mast to avoid their call. Since Kafka’s sirens are in fact, silent, Odysseus embodies a symbolic victory that is questionable, caught in an irreconcilable schism between truth and power, the iconic and the futile. Marching On operates within the same questionable margins by querying the body’s functionality as a source of aversion from the possible dangers of information overload. Articulated through the practice of self-imposed preservation, selfhood as a result, is visualised as a state of ‘abnormality’ that mirrors the haunting geopolitical lens, which accelerates indifference and inequalities of power.
Πορεία Ασφαλείας